Attorney General forces Infectious Diseases Society of America to redo Lyme guidelines due to flawed development process. Issue 5 (30th April 2009) - Johnson, L; Stricker, R B
Abstract : Lyme disease is one of the most controversial illnesses in the history of medicine. In 2006 the Connecticut Attorney General launched an antitrust investigation into the Lyme guidelines development process of the Infectious Diseases Society of America (IDSA). In a recent settlement with IDSA, the Attorney General noted important commercial conflicts of interest and suppression of scientific evidence that had tainted the guidelines process. This paper explores two broad ethical themes that influenced the IDSA investigation. The first is the growing problem of conflicts of interest among guidelines developers, and the second is the increasing centralisation of medical decisions by insurance companies, which use treatment guidelines as a means of controlling the practices of individual doctors and denying treatment for patients. The implications of the first-ever antitrust investigation of medical guidelines and the proposed model to remediate the tainted IDSA guidelines process are also discussed.